Endogenous Endophthalmitis in the American and Korean Population: An 8-year Retrospective Study. (19th May 2018) - Cho, Heeyoon; Shin, Yong Un; Siegel, Nicole H.; Yu, Hyeong Gon; Sobrin, Lucia; Patel, Achal; Durand, Marlene L.; Miller, Joan W.; Husain, Deeba
ABSTRACT: Purpose : To study the clinical features of endogenous endophthalmitis (EE) in sample patient populations from the USA and South Korea over an 8-year period. Methods : We reviewed data from 128 eyes of 60 American and 48 Korean patients diagnosed with EE and compared their clinical characteristics. Results : Fungemia and liver abscess were the most common extraocular infection sources among American (26.7%) and Korean patients (33.3%), respectively. Klebsiella pneumoniae and Candida species were the most common pathogens of EE in the Korean and the American patients, respectively. Endophthalmitis caused by fungi had a better visual prognosis than that caused by bacteria ( p = 0.001). Vitrectomy was beneficial for eyes with EE due to virulent bacteria presenting with worse than counting finger vision. Conclusions : The predisposing conditions and responsible organisms for EE vary in different regions of the world. The visual prognosis was strongly influenced by the underlying pathogen.